1993
DOI: 10.1111/j.1365-2133.1993.tb00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of hyperimmunoglobulinaemia D syndrome with erythema eievatum diutinum

Abstract: Hyperimmunoglobulinaemia D and periodic fever syndrome was observed in a female patient with erythema elevatum diutinum. The association of this skin disease with hyperimmunoglobulinaemia D may indicate a pathogenetic relationship. The skin lesions responded to dapsone therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 9 publications
2
10
0
1
Order By: Relevance
“…Henoch-Schö nlein purpura and erythema elevatum diutinum have been also reported in children with HIDS. 40,51 Erysipelaslike lesions are the most distinctive cutaneous lesion associated with FMF. 52 In published studies, 53,54 the observed frequency of these lesions varies from 3% to 46%, and they have been reported to occur in 15% to 20% of children.…”
Section: Commentmentioning
confidence: 99%
“…Henoch-Schö nlein purpura and erythema elevatum diutinum have been also reported in children with HIDS. 40,51 Erysipelaslike lesions are the most distinctive cutaneous lesion associated with FMF. 52 In published studies, 53,54 the observed frequency of these lesions varies from 3% to 46%, and they have been reported to occur in 15% to 20% of children.…”
Section: Commentmentioning
confidence: 99%
“…Hernandez-Cano et al reported the disappearance of EED lesions in a patient with a liver transplantation following a reduction in cyclosporin dosage [12]. However, EED lesions may not respond to dapsone, or if they do, recurrences are quite common [5,11,24,31,39]. It is possible that the marked fibrosis in late lesions may account for the lack of response to dapsone [8].…”
Section: Discussionmentioning
confidence: 91%
“…Other conditions reported to be associated include hyperimmunoglobulinemia D syndrome, cryoglobulinemia, myelodysplastic syndromes, abnormalities in the clotting mechanism, haematological malignancies, prostatic carcinoma, testicular lymphoma, viral and bacterial infections, rheumatic fever, HIV infection, inflammatory bowel disease, rheumatoid arthritis and peripheral ulcerative keratitis, relapsing polychondritis, Wegener's granulomatosis, and acro-osteolysis [1,9,10,16,18,23,24,37,39,40,41,42].…”
Section: Discussionmentioning
confidence: 96%
“…Ig have been reported in some cases, no uniformly successful treatment has been determined 3 . Notably, in a case accompanied with EED, dapson had a better effect than corticosteroid 27 . In 1999, the mevalonate kinase ( MVK ) gene on chromosome 12q24 was identified to be responsible for this disease 28,29 .…”
Section: Hereditary Periodic Fever Syndromesmentioning
confidence: 99%